AN EMPIRICAL STUDY ON OCCUPATIONAL STRESS IN BPO SECTOR, CHENNAI - Selvaraju, S. (IJRDO -Journal of Computer Science Engineering, 2017)
The survey revolves around the identifications of the level of stress. This research is beingconducted as a part of the individual development and strategies that organizations andindividuals adopt to overcome workplace stress.Retaining HR is a very tough job for any organization. It depends on various factors such assalary, perks, job security, organization process, authority and responsibility. It also dependson the perception and attitude of the individual in the organization.The survey is also conducted to find out the symptoms of stress which affects the individualregarding both personality and work. The survey focuses on various stress reductiontechniques which helps the individuals to reduce their stress level.